Overview of Physical Conditioning of Hockey Athlete - Haripah - Lawanis (Universitas Negeri Padang, 2019)
This study aims to determine the level of physical condition of West Sumatra hockey athletes. Popoulasi in this study are all West Sumatra hockey athletes, amounting to 20 people. Data is collected by conducting tests and measurements on each athlete's physical elements. The instruments used in this research were bleep test to measure aerobic endurance, running 50 meters to measure speed, Dodging run to measure agility and Flexiometer to measure flexibility. Data analysis was performed using descriptive analysis techniques through statistics (frequency tabulation). Conclusions from the study: From the analysis of the data it can be concluded that the level of physical abilities of West Sumatra hockey athletes is the best speed and flexibility, while the aerobic endurance and agility components are very low. Therefore physical abilities need to be improved through well-programmed training.